Quantum diffusion and tunneling in the solid hydrogens: a short review (Review Article): - Meyer, Horst (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The first observations 30 years ago of molecular clustering via quantum diffusion in solid H2 in nuclear magnetic resonance (NMR) and pressure experiments are described. A previous review on quantum diffusion and tunneling up to 1986 is updated to reflect progress in the last ten years. In particular I review the effect of clustering on heat capacity in solid D2 and on the thermal conductivity in solid H2. The configurational relaxation time observed in D2 at 1.75K is found to scale with that in H2 at the same temperature in terms of the predictions of ortho-para resonant conversion-induced hopping. The relaxation times measured simultaneously on the same sample in NMR and conductivity experiments reflect different configurational processes. The theory of molecular hopping and pairing in solid H2 is outlined and compared with experiments. The tunneling frequency of HD in solid H2 deduced from transverse and longitudinal NMR relaxation experiments between 0.03 and 14K is discussed. The hopping of ortho-H2, invoked as a mechanism in the enhanced ortho-para conversion in presence of O2 impurities, is mentioned. Finally, recent tunneling results for H, D and H2- anions in solid H2 during the studies of low temperature reaction dynamics are also briefly described. In the Appendix, the hopping frequency determination in HD from NMR transverse relaxation time measurements is reviewed.